(untitled) (Journal of Forest and Livelihood, 2018)
Countries in the Hindu Kush Himalaya (HKH) region have historically taken diverse initiatives towards sustainable forest management (SFM) aimed at conserving critical ecosystems. To protect resources by regulating access to these resources, indigenous people and local communities of the HKH region have developed diverse and well-established norms and procedures. Given the rich diversity in ecology and society in the region, the specific institutional and technological practices and innovations are also diverse. At the same time, most of the countries in the region have also actively involved in Reducing Emissions fromDeforestation and forest Degradation and the role of conservation, sustainable management of forests and enhancement of forest carbon stocks (REDD+) readiness process.